2012
DOI: 10.4236/jep.2012.328110
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Bacteriological Quality of the Vegetable Watering Water in the Dschang Town, Cameroon

Abstract: Market gardening, in the swampy lowlands of the Dschangcity, plays an important role in terms of providing employment, and supply the city with fresh products. However, waterborne diseases, which occur in the city, are both attributed to the bad quality of drinking water and sanitation practices. This work aims to characterize watering waters of crop, to assess the health risks associated with the use of these waters. Water from eleven streams and five wells used to irrigate crops were sampled and analyzed onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Its pits and crevices retain dirt containing organisms which may not be easily removed by slight washing. Recent studies in Cameroon [25, 26, 28] report that these vegetables are irrigated with fecally polluted water. Six bacteria species were isolated with Staphylococcus aureus predominating.…”
Section: Discussionmentioning
confidence: 99%
“…Its pits and crevices retain dirt containing organisms which may not be easily removed by slight washing. Recent studies in Cameroon [25, 26, 28] report that these vegetables are irrigated with fecally polluted water. Six bacteria species were isolated with Staphylococcus aureus predominating.…”
Section: Discussionmentioning
confidence: 99%
“…Regrettably, in such farming conditions, vegetables are frequently overflooded (with mud and domestic waste) during the raining seasons (March to October) (Akoachere et al, 2018;Ntangmo et al, 2012) or directly exposed to dust and/or domestic waste during the dry seasons (mid-October to March). Ntangmo et al ( 2012) further reported that several pit latrines and septic tanks are designed in such a way that their contents are emptied directly into the above-mentioned rivers and streams.…”
Section: Resultsmentioning
confidence: 99%
“…In Cameroon, leafy vegetables are currently the third product of the gardening sector, that is, after onions and tomatoes (Bayi et al, 2020). Market gardening employs over 60% of Cameroon's rural and peri-urban population and an estimated 2,832,000 tons of vegetables are produced annually (Abang et al, 2013;Asongwe et al, 2014;FAO, 2020b;Ntangmo et al, 2012). Several research (Akoachere et al, 2018;Tsama et al, 2015) have demonstrated that leafy vegetables cultivated and consumed in Cameroon could be highly infected with pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the waters in these marshes not only serve as a dumping ground for all kinds of rubbish but also receive almost all the wastewater produced in the city, where sanitation systems are almost nonexistent (Tchuikoua et al, 2016). This can compromise the quality of the water that is used without any prior treatment for the production of vegetable crops, some of which are consumed raw (Kouam et al, 2010;Ntangmo Tsafack et al, 2012, 2019b. This practice can be a risk factor for farmers and consumers of harvested products as it can lead to the contamination of market gardens produced by microorganisms, some of which can be dangerous for consumers (Ntangmo Tsafack et al, 2012, 2019bToe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This can compromise the quality of the water that is used without any prior treatment for the production of vegetable crops, some of which are consumed raw (Kouam et al, 2010;Ntangmo Tsafack et al, 2012, 2019b. This practice can be a risk factor for farmers and consumers of harvested products as it can lead to the contamination of market gardens produced by microorganisms, some of which can be dangerous for consumers (Ntangmo Tsafack et al, 2012, 2019bToe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%